Comparative study on polyimides derived from isomeric diphenylsulfonetetracarboxylic dianhydrides. (May 2013) - Pei, Xueliang; Chen, Guofei; Hou, Yijia; Fang, Xingzhong
In this study, three diphenylsulfonetetracarboxylic dianhydride (DSDA) isomers namely 2, 2′, 3, 3′-DSDA (3, 3′-DSDA), 2, 3, 3′, 4′-DSDA (3, 4′-DSDA) and 3, 3′, 4, 4′-DSDA (4, 4′-DSDA) were prepared from the corresponding diphenylthioethertetracarboxylic dianhydride isomers. Based on the three DSDA isomers, a series of isomeric polyimides were prepared. The properties, such as film-forming ability, solubility, wide-angle x-ray diffraction, thermal and mechanical properties as well as rheological behavior, were compared among the isomeric polyimides. It was found that 4, 4′-DSDA-based polyimides had much better film-forming ability than 3, 3′-DSDA- and 3, 4′-DSDA-based polyimides. 3, 4′-DSDA-based polyimides had better solubility than 3, 3′-DSDA- and 4, 4′-DSDA-based polyimides. Furthermore, for a given diamine, the glass transition temperatures of the polyimides from the three DSDA isomers decreased in the order of 3, 3′-DSDA > 3, 4′-DSDA > 4, 4′-DSDA, while the 5% weight loss temperatures in both air and nitrogen atmospheres of the polyimides mainly increased in the order of 3, 3′-DSDA < 3, 4′-DSDA < 4, 4′-DSDA. Moreover, 3, 4′-DSDA- and 4, 4′-DSDA-based polyimides showed much better melt stability than 3, 3′-DSDA-based polyimide.